Strengthening the linguistic reflection of students through the study of the nearby linguistic landscape (Educational Knowledge, 2024)
This article outlines a pedagogical endeavor undertaken with university students across diverse disciplines in the initial courses of a university in Asunción. Executed within the framework of the Writing Techniques course, the objective was to instigate linguistic contemplation among students. The method employed involved delving into the linguistic landscape (LL), specifically focusing on commercial signage in the students’ residential areas. Beyond cultivating observational skills, data collection, and image analysis in the local milieu, the initiative sought to forge an immersive pathway for nurturing linguistic consciousness. It aspired to extend beyond the classroom confines, foster an appreciation for one’s contextual backdrop, and discern the linguistic and cultural idiosyncrasies within each community.The study honed in on the intricacies of word usage, the structural nuances of commercial nomenclature, and the linguistic choices embedded in their nomenclature. The outcomes proved affirmative, prompting the exploration of the amassed image corpus for more expansive research endeavors and setting the stage for ongoing enhancements and innovations in future practices
Keywords: Oral and written communication; linguistic landscape; pedagogical practice; linguistic reflection